Deficits in high- (>60 Hz) gamma-band oscillations during visual processing in schizophrenia - Gruetzner, Christine; Wibral, Michael; Sun, Limin; Rivolta, Davide; Singer, Wolf; Maurer, Konrad; Uhlhaas, Peter (Frontiers in Human Neuroscience, 2013)
Current theories of the pathophysiology of schizophrenia have focused on abnormal temporal coordination of neural activity. Oscillations in the gamma-band range (> 25 Hz) are of particular interest as they establish synchronisation with great precision in local cortical networks. However, the contribution of high gamma (> 60 Hz) oscillations towards the pathophysiology is less established. To address this issue, we recorded magnetoencephalographic (MEG) data from 16 medicated patients with chronic schizophrenia and 16 controls during the perception of Mooney faces. Magnetoencephalographic data were analysed in the 25-150 Hz frequency range. Patients showed elevated reaction times and reduced detection rates during the perception of upright Mooney faces while responses to inverted stimuli were intact. Impaired processing of Mooney faces in schizophrenia patients was accompanied by a pronounced reduction in spectral power between 60-120 Hz (effect size: d = 1.26) which was correlated with disorganised symptoms (r = -.72). Our findings demonstrate that deficits in high gamma-band oscillations as measured by MEG are a sensitive marker for aberrant cortical functioning in schizophrenia, suggesting an important aspect of the pathophysiology of the disorder.